IMPLEMENTATION OF NET-ZERO ENERGY BUILDING CONCEPT IN THE DESIGN FACADE ARCHITECTURE BUILDINGS IN CENTRAL JAVA - Ghaasyiyah, Khansa Nur; Gandarum, Dedes Nur; Walaretina, Rita (Jurnal Arsitektur ARCADE, 2021)
Abstract: Issues relating to conventional energy and environmental sustainability is a hot topic that has been often discussed in today's developing world. Researchers have predicted that in the coming years, numerous non-renewable resources would be scarcer and harder to get access to. This phenomenon would cause a detrimental influence on energy use in the future, resulting in the need for the development of alternative energy resources and implementation of energy conservation energy efficiency policies in every construction design. One of the most essential elements in constructions that have great influence in resolving this problem is the construction facades. Therefore, this research will focus on types of construction facade designs using the NZEB concept approach. The methodology used in this research is analytical descriptive by using case studies that relate to the construction of Net-Zero Energy Building, namely: BCA Academy, ENERPOS, PT. Ungaran Sari Garments, NUS School of Design & Environment 4, dan CIC Zero Carbon Park. The purpose of this research is to identify various types of innovation faÃ§ade designs of NZEB technologies that could be applied in construction that resides in Central Java considering the area has a tropical climate. This research also proves that construction that resides in warm climates prefers to use technologies that could prevent and reduce the fallout of sun radiation towards its buildings without sacrificing any natural light and takes advantage of the wind to minimalize the usage of frosting energy in buildings.Abstrak Isu mengenai krisis energi konvensional dan kelestarian lingkungan menjadi perhatian khusus yang marak diperbincangkan dalam perkembangan dunia saat ini. Telah diprediksi oleh sejumlah ilmuan bahwa dalam beberapa tahun kedepan, sumber-sumber alam tak terbarukan akan sulit dan langka untuk dikonsumsi. Masalah ini akan menimbulkan dampak yang sangat besar terhadap penggunaan energi di masa depan, sehingga diperlukannya pengembangan teknologi yang dapat menghasilkan sumber-sumber energi alternatif terbarukan dan implementasi kebijakan efisiensi energi di setiap rancangan bangunan. Elemen penting pada bangunan yang memiliki pengaruh besar dalam mengatasi permasalahan tersebut adalah fasad bangunan. Maka penelitian ini difokuskan pada macam-macam desain fasad bangunan dengan Konsep NZEB. Metodologi yang digunakan dalam penelitian adalah metode deskriptif analitis dengan menggunakan studi kasus bangunan Net-Zero Energy Building, yaitu gedung BCA Academy, ENERPOS, PT. Ungaran Sari Garments, NUS School of Design & Environment 4, dan CIC Zero Carbon Park. Tujuan dari penelitian ini adalah untuk mengidentifikasikan berbagai macam inovasi desain fasad teknologi NZEB yang dapat diterapkan pada bangunan di Jawa Tengah yang iklim tropis basah. Penelitian ini juga menunjukkan bahwa bangunan di daerah beriklim panas lebih menggunakan teknologi yang dapat mencegah atau mengurangi jatuhnya radiasi matahari pada bangunan tanpa mengorbankan pencahayaan alami dan memanfaatkan angin untuk meminimalisir penggunaan energi pendingin pada bangunan.